Entrepreneurship Education and Previous Work Experience on Business Creation in Nigeria - Ajayi, Omobola (Archives of Business Research, 2020)
The study examined the effects of entrepreneurship and previous work experience on business creation in Nigeria among students of Ekiti State University. The research adopted a descriptive of survey research. The total population for the study was 9250 gotten from the various registries in all the faculties of the university. The sample size for the research was 400 through the Taro and Yamane (1992) model. Result of the regression estimation revealed that coefficient estimates of 0.287 and 0.631 with the probability values of 0.493 and 0.142 for entrepreneurship education and prior work experience exert a positive impact on business creation among undergraduate students of Ekiti State University. The result reflects that increase in the level of entrepreneurship education and prior work experience will trigger a corresponding increase in the level of business creation among students of Ekiti state university to the tune of 0.287, 0.631 in terms of business creation score. Based on the discoveries and the analysis conducted in the study, it can be concluded that entrepreneurship education with prior work experience only contributes mildly to business creation among undergraduate student in Ekiti state. Prior exposure to the world of business encourages undergraduate students to create a business of their own.